2022
DOI: 10.14309/ajg.0000000000001951
|View full text |Cite
|
Sign up to set email alerts
|

Intrapancreatic, Liver, and Skeletal Muscle Fat Depositions in First Attack of Acute Pancreatitis Versus Health

Abstract: INTRODUCTION: Increased intrapancreatic fat deposition (IPFD) has emerged as a harbinger of pancreatic cancer and chronic pancreatitis. Although it is well recognized that diseases of the exocrine pancreas often lie on a continuum (with acute pancreatitis preceding the development of chronic pancreatitis and/or pancreatic cancer), whether increased IPFD predisposes to acute pancreatitis is unknown. This study aimed to compare fat depositions in the pancreas (as well as the liver and skeletal muscle) between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Subgroup analyses stratified by the diagnosis of diabetes and obesity did not reveal significant interactions. Recent studies have observed an association between intrapancreatic fat disposition and the development of acute pancreatitis, even after adjusting for multiple variables including fasting plasma glucose and BMI ( 43 , 44 ). BMI has been considered a poor proxy for intrapancreatic fat deposition ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses stratified by the diagnosis of diabetes and obesity did not reveal significant interactions. Recent studies have observed an association between intrapancreatic fat disposition and the development of acute pancreatitis, even after adjusting for multiple variables including fasting plasma glucose and BMI ( 43 , 44 ). BMI has been considered a poor proxy for intrapancreatic fat deposition ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Limitations of this study include its cross-sectional design, as no causal inference can be made from it. [39][40][41][42] Longitudinal studies are now warranted to investigate temporal changes in bile acids and ectopic fat deposition in order to establish causality. 43,44 As the study was the first to investigate total bile acids in the context of IPFD and SMFD, 5 we were unable to estimate the required sample size prior to the commencement of the study.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Intrapancreatic fat deposits are a precursor to pancreatic cancer in patients with pancreatitis. 8 Mean lipid and uric acid levels are significantly higher in patients with PS than in patients without PS. 9 The prevalence of PS is elevated in patients with hyperlipidemia.…”
Section: Introductionmentioning
confidence: 94%
“…Increasing evidence suggests that PS is associated with type 2 diabetes, metabolic syndrome, atherosclerosis, acute severe pancreatitis, and pancreatic cancer. , PS can be an initial indicator of “ectopic fat deposition,” which occurs before nonalcoholic fatty liver disease . Intrapancreatic fat deposits are a precursor to pancreatic cancer in patients with pancreatitis . Mean lipid and uric acid levels are significantly higher in patients with PS than in patients without PS .…”
Section: Introductionmentioning
confidence: 99%